2019
DOI: 10.1155/2019/8575219
|View full text |Cite
|
Sign up to set email alerts
|

A New Solution Approach for Maritime Surveillance Operation: The Case of Aegean Sea

Abstract: Nowadays, many people illegally migrate to other countries by sea because of warfare or internal conflict in their countries, and thousands of people lose their lives for this reason. Besides, illegal trafficking of drugs or historical artifacts, illegal fishing, and various terrorist activities are conducted through the seas. Maritime surveillance operations are of great importance to prevent all these threats and maintain national security. In this study, the problem of surveillance and exploration which is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…In a study conducted by ˙Işleyen, Uçar, and Balo [18] on the identification of irregular migrant boat crossings in the Aegean Sea, an algorithm based on simulated annealing was proposed to solve the problem and the algorithm was tested on various scenarios. Remarkably, it was observed that within the allocated solution time, the algorithm consistently detected all targets in the least possible time for all 50 different scenarios.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a study conducted by ˙Işleyen, Uçar, and Balo [18] on the identification of irregular migrant boat crossings in the Aegean Sea, an algorithm based on simulated annealing was proposed to solve the problem and the algorithm was tested on various scenarios. Remarkably, it was observed that within the allocated solution time, the algorithm consistently detected all targets in the least possible time for all 50 different scenarios.…”
Section: Literature Reviewmentioning
confidence: 99%